Ability of students in completing mathematical story problems - Putri Khoerunnisa (Mitra Palupi, 2021)
Background: Elementary school must be a strong foundation to reach a higher level of education. This is inseparable from the beginning of the level of education starting from early childhood and kindergarten because it is a level of education to start the formation of children's character. One of the subjects given at every level of education is Mathematics. Mathematics is one of the sciences that has an important role in shaping the mindset of students, because in mathematics students are required to have the ability to think logically, systematically, analytically as well as problem solving abilities. Various attempts have been made by the teacher in increasing the ability of students to understand mathematics subjects. However, the expected results are still not optimal, even the learning and teaching process becomes unpleasant and tends to be boring for students. One of the math problems that is often found is the difficulty of students in solving story problems. Even though the story problem is a form of evaluation of the ability of students in understanding the basic concepts of mathematics that have been learned, in the form of questions about applying formulas. Purpose: This study aims to examine the extent to which students' ability to work on math story problems. It could help teachers to find out the problems of students in working on math story problems and make students able to solve problems in the form of stories with the right method. Design and methods: The research method used is qualitative methods. Qualitative research is research in accordance with the data, utilizing existing theories as explanatory material. Results: The results of this study show that there are many problems in students working on math story problems, and the teacher's methods during learning must be improved so that students can understand